2016
DOI: 10.1002/anie.201602795
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Gold Nanoparticles with Size‐Independent Emission

Abstract: Size-independent emissions have been widely observed from ultrasmall thiolated gold nanoparticles (AuNPs) but remain a mystery in fundamental understanding of photoluminescence mechanisms of noble metals on the nanoscale. Herein, we report a correlation between emission wavelengths and local binding geometries of a thiolate ligand (glutathione) on AuNPs with identical size (~2.5 nm) but two distinct emission wavelengths. Using circular dichroism, X-ray absorption and fluorescence spectroscopies, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
111
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 40 publications
(50 reference statements)
8
111
3
Order By: Relevance
“…The high similarity observed in excitation and emission of Cys-AuNPs and Gly-Cys-AuNPs suggested that optical transitions among AuNPs with these two different surface coatings were mainly governed by Au-S charge transfer. 13,14 …”
mentioning
confidence: 99%
“…The high similarity observed in excitation and emission of Cys-AuNPs and Gly-Cys-AuNPs suggested that optical transitions among AuNPs with these two different surface coatings were mainly governed by Au-S charge transfer. 13,14 …”
mentioning
confidence: 99%
“…To obtain high-quality AuNCs, a succession of synthetic methods has appeared, including chemical reduction [18], electroreduction [31], photoreduction [32], bioreduction [33,34], and sonochemical method [35]. Generally, there are two main strategies for preparing AuNCs.…”
Section: Synthesis Of Auncsmentioning
confidence: 99%
“…1 Over the past decade, various renal-clearable luminescent metal NPs have been developed by tuning their particle size, surface chemistry, or valence state of the metal to unravel their new optical features and emission mechanisms, [2][3][4][5] which would extend their future bioapplications. The further rational engineering of the renalclearable metal NPs from both surface chemistry and selfassembly would greatly reduce the side effects, and these engineering NPs can be used as imaging contrast agents in the fields of single or multimodal biosensing, bioimaging and molecular tracking in various biosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The further rational engineering of the renalclearable metal NPs from both surface chemistry and selfassembly would greatly reduce the side effects, and these engineering NPs can be used as imaging contrast agents in the fields of single or multimodal biosensing, bioimaging and molecular tracking in various biosystems. For example, the glutathione-coated luminescent gold NPs (GS-AuNPs) with emission wavelength ranging from visible to near infrared region (NIR) window have been successfully synthesized, and even the dual-emissive NPs with both visible and NIR emission integrated in the same small-sized NPs could be achieved by facilely adjusting their structural parameters, such as the coverage of surface ligands and valence state, [2][3][4] which can be applied in noninvasive disease-related imaging in both in-vitro and in-vivo levels. [6][7][8][9] Recently, instead of paying much attention to improve the chemical functionalities of NPs to obtain better performance in animal models, researchers have realized the importance of the in-vivo behaviors such as pharmacokinetics and biodistribution of these NPs, which is crucial to evaluate their nanotoxicity in the preclinical trials to achieve their clinical translation.…”
Section: Introductionmentioning
confidence: 99%